School Curriculum (KSP) Fast Track: Integration of Google Tools and Artificial Intelligence in KSP Development - Kamila Harahap (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study addresses the challenge of creating an authentic and adaptive school curriculum (KSP) in Indonesia, where administrative burden often leads to generic